Radio and infrared recombination studies of the southern massive star forming region G333.6-0.2 t - Fujiyoshi, T; Smith, C; Caswell, J; Moore, T; Lumsden, S; Aitken, D; Roche, P (2006)
We present high spatial resolution radio and near-infrared hydrogen recombination line observations of the southern massive star forming region G333.6-0.2. The 3.4-cm continuum peak is found slightly offset from the infrared (IR) source. The H90α spectra show for the first time a double-peak profile at some positions. The complex velocity structure may be accounted for by champagne outflows, which may also explain the offset between the radio and IR sources. The 2.17-μm Brγ image and H90α map are combined to construct an extinction map which shows a trend probably set by the blister nature of the H ii region. The total number of Lyman continuum photons in the central 50-arcsec is estimated to be equivalent to that emitted by up to 19 O7V stars. © 2006 RAS.